THIRD GENERATION UNIVERSITY: B. CLARK AND J. WISSEMA - Nikita V. Golovko; Ol'ga V. Zinevich; Elizaveta A. Ruzankina (Высшее образование в России)
The paper aims to analyze the Clarks' concept of entrepreneurial university within the 3rd generation university theory by J. Wissema. Originally the Clarks' entrepreneurial university is defined by the set of consistent practices (independence from the governmental funding, management quality, entrepreneurial culture etc.) that demonstrate the potential to commercialize an obtained knowledge. The useful interpretation of entrepreneurial university within the Wissema's 3rd generation university theory gives an opportunity to evaluate the quality of internal policies that the university established to develop the entrepreneurial culture. The very fact that within the Wissema's concept the reasons of necessity of the develop of the entrepreneurial culture are not based on the external conditions (requirements to advance the development of the innovation economics, the technology transfer etc.), but are based on the internal requirements to fight the rivalry for funding, talented academics, prospective students etc., helps to move from the discussion of the development of the entrepreneurial activities within the third mission framework to the discussion of the transformation of the first mission by the bringing up to date the curricula and pedagogy towards the entrepreneurial culture shaping.